2016
DOI: 10.1097/fbp.0000000000000205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sex and remifentanil dose on rats’ acquisition of responding for a remifentanil-conditioned reinforcer

Abstract: Opioid-conditioned reinforcement is thought to exacerbate opioid abuse and dependence. Sex/gender can influence opioid abuse behaviors, but the effects of sex/gender on opioid-conditioned reinforcement, specifically, are unclear. In this study we compared new-response acquisition with opioid-conditioned reinforcement in male and female rats. First, separate groups received response-independent remifentanil injections (0.0-32.0 μg/kg, IV) and presentations of a light–noise stimulus. In experimental groups, inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 80 publications
3
9
0
Order By: Relevance
“…We found that animals that had a Paired Pavlovian conditioning history showed a higher level of active responding relative to animals assigned to the Random control group, in particular for animals conditioned with 3.2 and 10.0 μg/kg/infusion of remifentanil. These findings are consistent with Bertz and colleagues (2013;2016) and indicate that a Paired Pavlovian conditioned history engendered a higher level of conditioned reinforcing properties. We extended the findings of Bertz and colleagues by characterizing persistence and by using an effect size analysis.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found that animals that had a Paired Pavlovian conditioning history showed a higher level of active responding relative to animals assigned to the Random control group, in particular for animals conditioned with 3.2 and 10.0 μg/kg/infusion of remifentanil. These findings are consistent with Bertz and colleagues (2013;2016) and indicate that a Paired Pavlovian conditioned history engendered a higher level of conditioned reinforcing properties. We extended the findings of Bertz and colleagues by characterizing persistence and by using an effect size analysis.…”
Section: Discussionsupporting
confidence: 92%
“…These data should be interpreted with a consideration in mind that we did not include a control condition in which saline was used (instead of remifentanil) during the Pavlovian conditioning phase. We determined the range of doses of remifentanil based on the findings of Bertz et al (2016), who did include a saline control. They found that pairing saline infusions with stimulus presentations did not engender the stimulus with conditioned reinforcing properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, consistent with former investigations, there do not appear to be any sex differences in either the acquisition or expression of motivated behaviours to conditioned stimuli. [2,12]. The failure of a D 4 agonist to alter behaviour here is in some regards surprising, in that a canon of evidence implicates D 4 receptor dysfunction in multiple disease states that are characterised by inappropriate or maladaptive attributions of salience.…”
Section: Discussionmentioning
confidence: 86%